PENGEMBANGAN MODEL OPTIMASI WADUK PANDANDURI UNTUK PEMENUHAN KEBUTUHAN AIR IRIGASI DI LOMBOK TIMUR NUSA TENGGARA BARAT - , Ratih Kusuma Hartini ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Water supply from South Lombok Interconnection Irrigation Network has not able to meet water demand of irrigation areas in South Lombok including Palung and Gambir River Irrigation System. In order to overcome this problem the government has been building Pandanduri Reservoir to increase the water supply availability. The reservoir is prepared as the regulator of water resources management in Pandanduri and surrounding areas. The water allocation plan requires accurate information about the reservoir water supply capacity according to the croping pattern, cropping schedule and characteristics of water availability. The previous study reported that there is potential of additional water availability from ponds water storage and reuse water of return flow in the irrigation systems. Therefore, it requires more detailed study to determine the optimum capacity of the Pandanduri Reservoir in utilizing water based on some proper perfomance indicators of reservoir operation. This study is aimed to optimize water utilization of Pandanduri Reservoir in fulfilling irrigation water demand of Palung River Irrigation System and the required additional water to Gambir River Irrigation System. Optimization model was formulated by using Linear Programming method, which is combined with a simulation model to control release from reservoir within the operating rule. The capacity water utilization is measured by multi-criteria aspects, i.e. annual cropping intensity, k factor as the ratio between actual release and target release according to water demand, and the reliability of reservoir operation. The optimization and simulation were run simultaneously using input 10 years historical record of half monthly inflow discharge observed at Suradadi water level gauge. The amount of outflow as the target release consists of water demand for flushing and irrigation with existing cropping pattern (paddy â paddy/palawija/tobacco â palawija/tobacco). Potential of additional water availability from ponds water storage and return flow was taken into account for calculating net irrigation water demand. Result of global water balance analysis without taking the additional water availability into account shows 38.7 MCM annual deficit of water from the total amount of the target at annual cropping intensity of 211%. While taking additional water availability into account yields 22.9 MCM annual surplus. Previous study (Azis, 2012) showed that the available water in Pandanduri Reservoir was able to meet the irrigation water demand with maximum annual cropping intensity of 237.2% for 4,477 ha of command area and add water supply 30% of irrigation water demand of Pandanduri Irrigation Area to Gambir River Irrigation System. For that condition the k factor was 0.920 and the reliability of reservoir operations reached to 90%. Optimization results in this study shows an increase in maximum annual cropping intensity to 239.9% for 7,663 ha of command area including the exertion water to Gambir River Irrigation System that can be obtained by cultivating the first crop of paddy in the third week of September with existing cropping pattern. The optimum reservoir operation concludes that irrigation water supply capacity is characterized by average k factor of 0.879 and the operating reliability is 83.8%.